2016
DOI: 10.1037/dev0000148
|View full text |Cite
|
Sign up to set email alerts
|

Sleep arrangements, parent–infant sleep during the first year, and family functioning.

Abstract: The present longitudinal study addressed the ongoing debate regarding the benefits and risks of infant-parent co-sleeping by examining associations between sleep arrangement patterns across the first year of life and infant and parent sleep, marital and family functioning, and quality of mothers’ behavior with infants at bedtime. Patterns of infant sleep arrangements across the infants’ first year were derived from information obtained from 139 families at 1, 3, 6, 9, and 12 months of infant age in a U.S., cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 58 publications
3
43
0
Order By: Relevance
“…By contrast, solitary sleeping increased at 3 months (54%), outnumbered co-sleeping at 6 months (77%), and became dominant at 9 months (83%) and 12 months (83%). Consistent with past research (Hauck et al, 2008; McCoy et al, 2004; Morelli, Rogoff, Oppenheim, & Goldsmith, 1992; Teti et al, 2016), our data indicate that it is a culturally normative trend, particularly for European Americans, to move their infants into solitary sleep by 6 months of age.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…By contrast, solitary sleeping increased at 3 months (54%), outnumbered co-sleeping at 6 months (77%), and became dominant at 9 months (83%) and 12 months (83%). Consistent with past research (Hauck et al, 2008; McCoy et al, 2004; Morelli, Rogoff, Oppenheim, & Goldsmith, 1992; Teti et al, 2016), our data indicate that it is a culturally normative trend, particularly for European Americans, to move their infants into solitary sleep by 6 months of age.…”
Section: Resultssupporting
confidence: 91%
“…This suggests that solitary sleep by 6 months is a cultural preference for European American families. Together with the past reports that most American parents move their infants to a separate by 6 months (Hauck et al, 2008; McCoy et al, 2004; Morelli et al, 1992; Teti et al, 2016), it appears that it is the American cultural norm to refrain from co-sleeping beyond 6 months.…”
Section: Discussionmentioning
confidence: 89%
“…It also conflicts with other data that room-sharing is associated with more sleep disruption for mothers. 24,38 Our data showing shorter night sleep and shorter sleep bouts for infants who are room-sharing has potentially important consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Cosleeping (i.e., bed sharing, room sharing, or the combination of both) has also been examined in relation to infant sleep in accordance with the proposition that parental nighttime availability fosters infant's dependency on their parents to go or return to sleep and thus might lead to sleeping problems. When compared to mothers of solitary sleeping infants, mothers of cosleeping infants have reported more infant night wakings (e.g., Teti, Shimizu, Crosby, & Kim, ; Volkovich, Bar‐Kalifa, Meiri, & Tikotzky, ; Volkovich, Ben‐Zion, Karny, Meiri, & Tikotzky, ). Maternal reports of increased night wakings, however, were not supported by objective infant sleep measures: Use of actigraphy recordings revealed no differences in sleep disruption between cosleeping and solitary sleeping infants (Teti et al., ; Volkovich et al., , ).…”
Section: This Studymentioning
confidence: 99%
“…When compared to mothers of solitary sleeping infants, mothers of cosleeping infants have reported more infant night wakings (e.g., Teti, Shimizu, Crosby, & Kim, ; Volkovich, Bar‐Kalifa, Meiri, & Tikotzky, ; Volkovich, Ben‐Zion, Karny, Meiri, & Tikotzky, ). Maternal reports of increased night wakings, however, were not supported by objective infant sleep measures: Use of actigraphy recordings revealed no differences in sleep disruption between cosleeping and solitary sleeping infants (Teti et al., ; Volkovich et al., , ). In another study, at 4 months of age, the longest mother‐reported single sleep period for solitary sleepers was longer than that for room sharing infants; by 9 months of age, infants who had become solitary sleepers before 4 months of age had relatively longer mother‐reported total sleep and single sleep periods compared to other infants (Paul et al., ).…”
Section: This Studymentioning
confidence: 99%